ANALYSIS OF THE CONSTRUCTION CHARACTER APPEARANCE AND GENDER ROLE OF THE DC AND MARVEL FEMALE SUPER HERO - Polchana, Fonthip; Fyeted, Kajohn; Apisuohachok, Warapan (Journal of MCU Nakhondhat, 2023)
The objective of this research was studying the construction character and gender roles of the female superheroes from Marvel and DC. By using qualitative research and concept of studying three dimension of character creation, consisting of a physiological dimension, Sociology dimension, and psychological dimension and combine with the principles of character design and interpretation to study the construction character and gender roles of five female superheroes character which be chosen and considered that have profile and prominent role appearance in the franchises superheroes movie. The result showed that the construction character appearance and gender role of five female superhero characters were created to be the human in various ways with a three dimension and principles character design which is presented throught from the symbols and color scheme to accompany the appearance costumes, special power and abilities, as well as setting up character backgrounds and link to characterizing the psychological dimensions of the gender roles that appear in the film, which contribute to the psychological perception conveyed that represents the different forms of female communication images who do not have qualities or identities perfectly as social standard expected. To respond underneath the business condition and American society context that supports the ideology of gender equality and criticizes the patriarchy system by rephrase the question about between men and women, push forward this issue to society to know that woman have a status inferior to men and there have the roles in the media that still limited, not as diverse as men.